Utilization Of Underwater Submersible Light Led To Fish Swimming Activity On Fixed Liftnet Operated In Mangrove - Husni Angreni; Ibnu Malkan Hasbi; Jumrawati Jumrawati (Sangia Publishing, 2020)
Fixed chart fishing focuses on utilization of light aids for attract fish. Underwater submersible light ((Lacuda) LED is one of the assistive technologies that are environmentally friendly, be the subject of study in determining the characteristics of the movement or fish swimming groupings based on the operating time of the fishing gear and can be detected by hydroacoustic devices. The research method used is descriptive exploratory method by participating in fishing operations in the waters of Laikang Bay from April to September 2020. The results of the observations made at 18:00-05:00 Wita every trip shows that fish swimming activity after midnight tends to be higher than before midnight and at midnight. Based on the hydroacoustic detection of fish swimming activity in the form of solitary, medium and large groups at an average depth of 2-6 meters at 03:00-05:00 Wita. The amount of catch in hauling I is 138,4 Kg while hauling II is 157,3 Kg. The type of catch is small pelagic fish and demersal fish.